Philosophy of Science and Law: Integrating Science in Realizing the Art of a Just Life - Chifa Azyana Adly Meknesya; Amanda Zahra Marpaung (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
This study aims to examine the role of the philosophy of science in the legal realm as a means to realize a just way of life. Science plays a fundamental role in shaping, developing, and directing the legal system so that it is not merely normative, but also responsive to social dynamics. Through a philosophical approach, law is not seen simply as a set of rules, but as a reflection of core values such as justice, morality, and freedom. The research method used is a literature review, by analyzing key concepts of the philosophy of science and their application in law. The research findings show that the integration of various disciplines, such as philosophy, sociology, and psychology, contributes to a more comprehensive understanding of law, increases the effectiveness of law enforcement, and supports the development of a just and human-centered legal system. Furthermore, knowledge also plays a crucial role in legal education, both at the academic and practical levels, to produce competent human resources with high integrity. Thus, the philosophy of science emerges as an essential foundation in making law part of the art of living that is capable of bringing justice to society.